Liberalisation of international insurance operations : cross-border trade and establishment of foreign branches - Ishii, Hisaya (OECD ParisFR, 1999)
Provides an overview and analysis of the main measures and practices which affect international insurance operations in OECD countries. Focuses in particular on main insurance fields where obstacles to a full liberalisation may still exist, i.e. cross-border trade and establishment of foreign branches.